Mixing Between Jeans and Lace Fabrics to Design Wedding Dress Using Designing-on-the Mannequin Technique - Al Sheikh, Basma Abdel Mohsen (Advances in Social Sciences Research Journal, 2022)
Modelling or shaping on mannequin is a science and an art that has its scientific origins, in addition to the skill required to be acquired to master it. It depends on the individual's ability to innovate, his analytical ability and his skill in work that is characterized by quality, beauty and perfection to produce designs that perform their utilitarian and aesthetic functions. By modelling on mannequin, it is possible to add a shape and surface texture different from the shape and surface of the original material because the modelling method has great potential in this field by making suitable formation of the cloth on the mannequin. Rather, it can make more than one shape and more than one surface appearance for one type of cloth using modelling. This research seeks to analyze and characterize the aesthetic values in the use of jeans fabrics, in the innovative designs of international fashion designers; identify the relationship resulting from mixing jeans and laces in the design of the wedding dress using shaping on mannequin technique; measuring the degree of acceptance among specialists, and Saudi girls of age category (18-25) to the idea of wedding dresses made of lace and jeans fabrics. The research sample included a group of (14) faculty members specialized in the field as well as a group of (60) Saudi girls whose ages range between 18-25. Two questionnaires were used as a tool to measure the sample's attitudes towards the designs. It was found that the design has achieved great success in terms of concept and method of implementation and achieved a good mix of jeans and laces (tulle and lace) in a beautiful way.